Solutions to support the establishment and development of an international logistics center in Hai Phong city, Vietnam - Tran Hai Viet; Nguyen Thai Son; Nguyen Thi Tuyet Mai (Journal of State Management, 2024)
The study analyzes factors influencing the establishment and development of an international logistics center in Hai Phong, a vital port city in Vietnam. Hai Phong enjoys a strategic geographic location and a modern seaport system but needs improvements in infrastructure, policy, and workforce. The article proposes solutions to optimize the city's potential, including infrastructure development, enhanced international cooperation, policy improvements, workforce development, and technology application. These measures aim to position Hai Phong as a significant international logistics hub, contributing to the region's and the country's sustainable economic growth.